Immunoglobulin G Responses to a Panel of Candida albicans Antigens as Accurate and Early Markers for the Presence of Systemic Candidiasis - Clancy, Cornelius J. (American Society for Microbiology (ASM), 2008)
Despite shortcomings, cultures of blood and sterile sites remain the “gold standard” for diagnosing systemic candidiasis. Alternative diagnostic markers, including antibody detection, have been developed, but none are widely accepted. In this study, we used an enzyme-linked immunosorbent assay to measure serum antibody responses against 15 recombinant Candida albicans antigens among 60 patients with systemic candidiasis due to various Candida spp. and 24 uninfected controls. Mean immunoglobulin G (IgG) responses against all 15 antigens were significantly higher among patients with systemic candidiasis than among controls, whereas IgM responses were higher against only seven antigens. Using discriminant analysis that included IgG responses against the 15 antigens, we derived a mathematical prediction model that identified patients with systemic candidiasis with an error rate of 3.7%, a sensitivity of 96.6%, and a specificity of 95.6%. Furthermore, a prediction model using a subset of four antigens (SET1, ENO1, PGK1-2, and MUC1-2) identified through backward elimination and canonical correlation analyses performed as accurately as the full panel. Using the simplified model, we predicted systemic candidiasis in a separate test sample of 32 patients and controls with 100% sensitivity and 87.5% specificity. We also demonstrated that IgG titers against each of the four antigens included in the prediction model were significantly higher in convalescent-phase sera than in paired acute-phase sera. Taken together, our findings suggest that IgG responses against a panel of candidal antigens might represent an accurate and early marker of systemic candidiasis, a hypothesis that should be tested in future trials.